PARADIGMA AKUNTANSI SEKTOR PUBLIK: PERKEMBANGAN DAN TANTANGAN DI ERA DIGITAL - Meilani Al Rahmatia, Sinar Cahyani, Septi Ramdayanti, Cici Awalia (PT Wahana Global Education, 2025)
This study aims to analyze the influence of financial literacy on student consumer behavior. The phenomenon of The development of digital technology has brought fundamental changes to public sector accounting systems. The traditional paradigm, which was manual and administrative in nature, has shifted toward a more open, transparent, and technology-based system. Public sector accounting now focuses not only on financial reporting but also on enhancing public service delivery, budget efficiency, and citizen engagement through digital platforms. This transformation demands reform in policies, information systems, and human resource competencies. However, digitalization also presents several significant challenges. Technological infrastructure gaps, low levels of digital literacy, and issues of data security and privacy are major obstacles in implementing digital public accounting. Additionally, existing regulations have not fully adapted to technological advancements, making digital integration less than optimal. Therefore, institutional strengthening strategies, capacity building, and the formulation of responsive policies are essential to ensure that transparency and public accountability objectives are achieved effectively in the digital era.